Comparison of robotic-assisted and laparoscopic-assisted surgery in the treatment of children with Hirschsprung's disease: a systematic review and meta-analysis - Li, Zikang; Li, Wanfu; Wang, Haojun; Xu, Mengxue (Frontiers in Pediatrics, 2025)
BackgroundThis study aims to systematically evaluate the differences between robotic-assisted surgery (RAS) and laparoscopic-assisted surgery (LAS) in intraoperative parameters, postoperative complications, and prognostic outcomes for children with Hirschsprung's disease (HSCR). By conducting a meta-analysis, evidence-based insights for clinical practice were sought.MethodsFollowing PRISMA guidelines, PubMed, Embase, and Web of Science were searched up to May 10, 2025, to identify comparative studies of RAS and LAS for HSCR. Two reviewers independently screened literature and assessed quality using the Newcastle-Ottawa Scale (NOS). RevMan5.4 and STATA18 were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs), with heterogeneity and publication bias evaluated.ResultsSix studies involving 789 children (352 RAS, 437 LAS) were included. Meta-analysis showed significantly less intraoperative blood loss in the RAS group (OR = −6.45, 95%CI: −11.77 to −1.14, P = 0.02) but longer operative duration (OR = 19.74, 95%CI: 1.75–37.72, P = 0.03). No significant group differences were found in postoperative enterocolitis (OR = 0.66, 95%CI: 0.43–1.01, P = 0.06), anastomotic complications (OR = 0.71, 95%CI: 0.35–1.45, P = 0.35), soiling (OR = 0.79, 95%CI: 0.39–1.60, P = 0.51), adhesive intestinal obstruction (OR = 1.56, 95%CI: 0.22–11.32, P = 0.66), wound infection (OR = 0.77, 95%CI: 0.19–3.01, P = 0.70), incisional hernia (OR = 1.13, 95%CI: 0.20–6.40, P = 0.89), perianal infection (OR = 0.70, 95%CI: 0.40–1.23, P = 0.22), urinary retention (OR = 0.23, 95%CI: 0.01–3.59, P = 0.29), or gastrointestinal function recovery time (OR = −1.27, 95%CI: −3.70–1.15, P = 0.30). Hospital stay was significantly shorter in the RAS group (OR = −0.39, 95%CI: −0.69–−0.10, P = 0.009). Egger's test and funnel plot analysis indicated no significant publication bias (P = 0.987).ConclusionsRAS confers advantages in reducing intraoperative blood loss and shortening hospital stay, although it is associated with a longer operative duration. However, no significant difference in the incidence of postoperative complications was noted between RAS and LAS, a finding potentially attributable to the limited sample size. Furthermore, the currently elevated treatment cost of RAS may impede its widespread adoption due to economic limitations. Consequently, large-sample, multicenter randomized controlled trials with extended follow-up periods are warranted to validate long-term outcomes and conduct in-depth investigations into cost-effectiveness.Systematic Review RegistrationPROSPERO CRD420251051595.